Recent Advances in Methamphetamine Neurotoxicity Mechanisms and Its Molecular Pathophysiology - Shaobin Yu; Ling Zhu; Qiang Shen; Xue Bai; Xuhui Di (Behavioural Neurology)
Methamphetamine (METH) is a sympathomimetic amine that belongs to phenethylamine and amphetamine class of psychoactive drugs, which are widely abused for their stimulant, euphoric, empathogenic, and hallucinogenic properties. Many of these effects result from acute increases in dopamine and serotonin neurotransmission. Subsequent to these acute effects, METH produces persistent damage to dopamine and serotonin release in nerve terminals, gliosis, and apoptosis. This review summarized the numerous interdependent mechanisms including excessive dopamine, ubiquitin-proteasome system dysfunction, protein nitration, endoplasmic reticulum stress, p53 expression, inflammatory molecular, D3 receptor, microtubule deacetylation, and HIV-1 Tat protein that have been demonstrated to contribute to this damage. In addition, the feasible therapeutic strategies according to recent studies were also summarized ranging from drug and protein to gene level.